Judicative Analysis Towards Assets Protection which are Realties and Building of PT Timah (Persero) Tbk (A Case Study of Official Home) (The Indonesian Journal of Business Administration, 2013)
In the early nineties, PT Tambang Timah, recently known as PT TIMAH (Persero) Tbk is Stated - owned enterprise that its operational area control in Bangka and Belitung islands, Bangka Belitung Province and Singkep and also Karimun - Kundur, Riau Archipelago Province was involved in fluctuation by overwhelming of world supply of tin that caused world price of tin decrease drastically at that time. That condition made PT TIMAH was involved in financial difficulty for operational cost. Concerning that condition, PT TIMAH should take a company deliverance action by doing restructure. One of restructure action was doing assets transforming / resignation that were not relevant to the company main business. Principle approval of abrogation and displacing of fixed assets issued by letter of Monetary Minister of Indonesia Republic No. S-1218/MK.016/1992 dated October 13th, 1992 and by implementing according to regulation enterprise. Assets transformation that is official home was still get some problems with the Timah retirees up to now. The problem caused by the differences point of view in analyzing of the letter issued by Monetary Minister of Republic Indonesia, it will be mastery of the official home by retirees. Keywords: Realties and buildings. Judicative, Assets protection